GOVERNMENT HEGEMONY VS. DESA ADAT RESISTANCE: DYNAMICS OF REGULATING DESA ADAT IN BALI - Putu Gede Sridana; I Wayan P. Windia; I Nyoman Darma Putra; I Nyoman Suarka (Cultural Studies Doctorate Program, Postgraduate Program of Udayana University, 2024)
The government's strategy to promote desa adat (customary village) materialized through the implementation of Regional Regulation Number 4 of 2019 in Bali, fostering a dynamic interaction aimed at enhancing desa adat resilience. This study examines the dynamic forms of interaction between these institutions. Data were obtained utilizing a qualitative approach, including literature reviews, observations, and interviews. The data analysis results are described using theories of hegemony, ideology, discourse, and the power of knowledge. The research concludes that diverse forms of interaction between the government and desa adat encompass involvement in the formulation of desa adat regulations; participation in religious rituals and cultural activities; and relevance in financial governance. Theoretical findings suggest that power operates through interactions to assert dominance over desa adat by spreading discourse, knowledge, and ideological strategies. This article provides valuable insights for shaping regulations that better align with the identity and autonomy of desa adat. Keywords: dynamic interactions, desa adats, Regional Regulation Number 4/2019